Pliocene reservoir characteristics in the centre of Song Hong basin - Tran Thi Thanh, Thuy (Petrovietnam Journal, 2019)
This paper presents the results of petrography and core analysis, FMI and log interpretation to define Pliocene reservoir characteristics in the centre of Song Hong basin. The reservoirs, which are fine-thin sandstone layers interbedded with unconsolidated siltstone/claystone deposited in outer-shelf to deep marine, could be defined as fine to very fine grain size, good to very good sorting, sub-angular to sub-rounded grain shape. The Pliocene reservoir quality is fair to very good, featured by thin-bedded, weak consolidated, and almost primary porosity with good connection, sometimes filled by authigenic minerals. The effective porosity and permeability range from 20 - 30% and 2 - 1,000mD, respectively.